2020
DOI: 10.1186/s12957-020-02103-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of clinical toxicities of chemotherapy with fluoropyrimidines and oxaliplatin in colorectal cancer by DPYD and GSTP1 gene polymorphisms

Abstract: Background Fluoropyrimidines and platinum are still widely used for colorectal cancer (CRC) management. Several studies have reported that mutations of dihydropyrimidine dehydrogenase (DPYD) and glutathione S-transferase pi-1 (GSTP1) polymorphisms are related to chemotherapy-related adverse events. In the present study, we purposed to assess the impact of DPYD and GSTP1 variants on the toxicity of adjuvant chemotherapy risk among the Hakka population, minimize adverse events, and to maximize therapy outcome fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…According to the FDA, the toxicity caused by these drugs is distinguished by the development of mucositis, stomatitis or esophagopharyngitis, diarrhea (grade 3 or 4), palmar-plantar erythrodysesthesia (hand-foot syndrome), myelosuppression, hyperammonemic encephalopathy, and systemic toxicity. Toxicity grade 3 occurs in 25–30% of patients treated with this group of drugs [ 9 , 10 ], and is characterized by the development of neutropenia and leukopenia, vomiting, and skin ulceration [ 11 , 12 ]. Regarding systemic toxicity, in 1–18% of patients, one can observe the development of a spectrum of cardiac problems ranging from coronary ischemia, systolic left ventricular dysfunction, arrhythmias, and sudden death [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the FDA, the toxicity caused by these drugs is distinguished by the development of mucositis, stomatitis or esophagopharyngitis, diarrhea (grade 3 or 4), palmar-plantar erythrodysesthesia (hand-foot syndrome), myelosuppression, hyperammonemic encephalopathy, and systemic toxicity. Toxicity grade 3 occurs in 25–30% of patients treated with this group of drugs [ 9 , 10 ], and is characterized by the development of neutropenia and leukopenia, vomiting, and skin ulceration [ 11 , 12 ]. Regarding systemic toxicity, in 1–18% of patients, one can observe the development of a spectrum of cardiac problems ranging from coronary ischemia, systolic left ventricular dysfunction, arrhythmias, and sudden death [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Deng et al found that colorectal cancer patients with GSTP1 c.313A > G mutation who received treatment with fluoropyrimidines and oxaliplatin had an increased risk of severe vomiting (grade III/IV), but there was no relationship between the polymorphism and neutropenia. And it showed that GSTP1 c.313A > G mutation may be an independent risk factor for severe vomiting induced by chemotherapeutic drugs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 A growing number of genes and motifs have been reported to be associated with PPCT toxic responses or genetic alterations, including the glutathione S transferase Pi 1 (GSTP1) gene rs1695, methylenetetrahydrofolate reductase (MTHFR) gene rs1801133, xeroderma pigmentosum complementation group C (XPC) gene rs2228001, tumor protein p53 (TP53) gene rs1042522, and excision repair cross-complementation group 1 (ERCC1) gene rs3212986, which provides a broader perspective to facilitate the development of precision medicine. [12][13][14][15][16] In the present study, we recruited 244 patients recently diagnosed with cervical, ovarian, uterine, or fallopian tube cancer. SNPs at rs1695, rs1801133, rs2228001, rs1042522, and rs3212986, were characterized by performing multichannel fluorescence real-time quantitative polymerase chain reaction (PCR) on specimens of peripheral blood.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…The Human Genome Project has identified millions of SNPs; the corresponding relationships with responsiveness to drugs (including antitumor drugs) has received increasing attention 11 . A growing number of genes and motifs have been reported to be associated with PPCT toxic responses or genetic alterations, including the glutathione S transferase Pi 1 ( GSTP1 ) gene rs1695, methylenetetrahydrofolate reductase ( MTHFR ) gene rs1801133, xeroderma pigmentosum complementation group C ( XPC ) gene rs2228001, tumor protein p53 ( TP53 ) gene rs1042522, and excision repair cross‐complementation group 1 ( ERCC1 ) gene rs3212986, which provides a broader perspective to facilitate the development of precision medicine 12–16 …”
Section: Introductionmentioning
confidence: 99%